## cosec theta – cot theta whole square = 1-cos theta/1+cos theta

(Cosec-Cot)^2=1-Cos/1+Cos

L.H.S.= (Cosec-Cot)^2

(1/Sin-Cos/Sin)^2

(1-Cos)^2/(Sin)^2

(1-Cos)^2/Sin^2

(1-Cos)^2/(1-Cos2)

(1-Cos)^2/(1-Cos)(1+Cos)

(1-Cos)/(1+Cos)=R.H.S.

**More**

(Cosec-Cot)^2=1-Cos/1+Cos

L.H.S.= (Cosec-Cot)^2

(1/Sin-Cos/Sin)^2

(1-Cos)^2/(Sin)^2

(1-Cos)^2/Sin^2

(1-Cos)^2/(1-Cos2)

(1-Cos)^2/(1-Cos)(1+Cos)

(1-Cos)/(1+Cos)=R.H.S.

**More**

## 1 thought on “cosec theta – cot theta whole square = 1-cos theta/1+cos theta Class 10 Ex 8.4 Q 5 i”